2009
DOI: 10.1017/s0143385708001089
|View full text |Cite
|
Sign up to set email alerts
|

A characterization ofω-limit sets in shift spaces

Abstract: A set Λ is internally chain transitive if for any x,y∈Λ and ϵ>0 there is an ϵ-pseudo-orbit in Λ between x and y. In this paper we characterize all ω-limit sets in shifts of finite type by showing that, if Λ is a closed, strongly shift-invariant subset of a shift of finite type, X, then there is a point z∈X with ω(z)=Λ if and only if Λ is internally chain transitive. It follows immediately that any closed, strongly shift-invariant, internally chain transitive subset of a shift space over some alphabet ℬ is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 7 publications
1
39
0
Order By: Relevance
“…For an interval map f : I → I, a subinterval J ⊂ I is called a homterval if c / ∈ f n (J) for every n ≥ 0 and any local extremum c. Notice that tent maps T with slope λ ∈ (1, 2] have no homterval, since every subinterval expands under T until eventually it contains the critical point c. Lemmas 2.4, 2.5 and 2.6 are well-known [5,6,16,18]. We state them here as they will be of use in what follows.…”
Section: A Review Of Symbolic Dynamics For Tent Mapsmentioning
confidence: 99%
See 2 more Smart Citations
“…For an interval map f : I → I, a subinterval J ⊂ I is called a homterval if c / ∈ f n (J) for every n ≥ 0 and any local extremum c. Notice that tent maps T with slope λ ∈ (1, 2] have no homterval, since every subinterval expands under T until eventually it contains the critical point c. Lemmas 2.4, 2.5 and 2.6 are well-known [5,6,16,18]. We state them here as they will be of use in what follows.…”
Section: A Review Of Symbolic Dynamics For Tent Mapsmentioning
confidence: 99%
“…Furthermore, they have been the subject of many research articles [12,17,28,30], often in relation to their ω-limit sets [6,21,22,23,24]. In this paper we make several important observations about the behaviour of tent maps, allowing us to prove new results about the nature of their limit sets in relation to certain well-known dynamical properties.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is known that there are interval maps both with and without shadowing, and partial classifications exist in this context [11]. It has also been demonstrated that shifts of finite type [5] and Julia sets for certain quadratic maps [7,8] all exhibit shadowing .…”
Section: Preliminariesmentioning
confidence: 99%
“…Specifically, for several types of dynamical systems it is known that ( †) A closed set A is internally chain transitive if, and only if, there is some x with ω(x) = A. It is known that ( †) holds for shifts of finite type, topologically hyperbolic maps, a family of quadratic Julia sets, and certain interval maps, [5], [8], [7], and [3]. In fact, in [4], Barwell et al show that there are certain unimodal maps of the unit interval for which ( †) holds and certain other ones for which it fails.…”
Section: Introductionmentioning
confidence: 99%